Lattice gas methods for partial differential equations : a volume of lattice gas reprints and articles, including selected papers from the workshop on large nonlinear systems, held August, 1987 in Los Alamos, New Mexico /: a volume of lattice gas reprints and articles, including selected papers from the workshop on large nonlinear systems, held August, 1987 in Los Alamos, New Mexico. (2019) - Unknown
No abstract available